The Effectiveness of Using Emodemo Methods on Knowledge of Pregnant Women’s Nutritional Needs - Anggasari, Yasi; Mardiyanti, Ika (STRADA : Jurnal Ilmiah Kesehatan, 2020)
KEK in pregnant women can increase the risk of premature birth, low birth weight , maternal and infant mortality. Lack of knowledge about nutritional needs is one of the causes of KEK in pregnant women. The purpose of this study was to determine the effectiveness of using the emodemo method on knowledge of the nutritional needs of pregnant women. Research Pre-experimental design with one group pretest posttest desaign design. The population of all pregnant women at PMB Nanik Sidoarjo was 30 samples by means of purposive sampling carried out for 3 months, namely June-August 2020. Data collection was in the form of a questionnaire. Statistical test using the Wilcoxon Sign Rank Test. The statistical test results obtained a significance value of 0.000 (p value <0.005) which means that there is an effect of using the emodemo method on knowledge of the nutritional needs of pregnant women.